2016
DOI: 10.3747/co.23.3038
|View full text |Cite
|
Sign up to set email alerts
|

Fee-for-Service Cancer Rehabilitation Programs Improve Health-Related Quality of Life

Abstract: Background Rigorously applied exercise interventions undertaken in a research setting result in improved health-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A review of randomized controlled trials by a panel of clinical and research experts confirmed that during and after cancer treatment, exercise is safe and beneficial for reducing many common sequelae of cancer treatment, such as fatigue, increased body weight, healthrelated physical fitness, and health-related quality of life (HRQoL). 1 Although results of the effectiveness of community-based exercise programs have recently been published, [2][3][4][5][6][7][8] effective translation of this research into clinical oncology practice remains to be demon-…”
mentioning
confidence: 99%
“…A review of randomized controlled trials by a panel of clinical and research experts confirmed that during and after cancer treatment, exercise is safe and beneficial for reducing many common sequelae of cancer treatment, such as fatigue, increased body weight, healthrelated physical fitness, and health-related quality of life (HRQoL). 1 Although results of the effectiveness of community-based exercise programs have recently been published, [2][3][4][5][6][7][8] effective translation of this research into clinical oncology practice remains to be demon-…”
mentioning
confidence: 99%
“…A recent study showed that enrolment in a fee-for-service cancer-specific exercise programme (including paying for the initial fitness assessment) positively affected QoL in cancer survivors, increased self-reported exercise and reduced perceived barriers to PA [15]. Cancer United™ (a registered cancer support charity based in West Sussex, UK) developed a fee-for-service cancer-specific exercise programme (CU Fitter™) from cancer diagnosis onwards with no limit to duration of participation.…”
Section: Introductionmentioning
confidence: 99%
“…However, is evidence of benefit to fitness and quality of life enough to change clinical oncology practice and to make exercise programs an essential component of cancer care? Certainly, the evidence for fitness and quality-of-life benefits would seem sufficient for clinicians to at least recommend exercise to their patients and perhaps even to refer them to one of the growing number of community-based exercise programs for cancer survivors [5][6][7][8][9] . But what would it take for cancer centres themselves to integrate high-quality exercise programs into clinical cancer care?…”
mentioning
confidence: 99%